2016
DOI: 10.1039/c6ay01512c
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and ultra-sensitive detection of foodborne pathogens by using miniaturized microfluidic devices: a review

Abstract: Identification and quantification of foodborne pathogens are becoming increasingly important to public health and food safety since the majority of foodborne illnesses and deaths are caused by pathogenic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 139 publications
(150 reference statements)
0
23
0
Order By: Relevance
“…Based on the results from the AFM study, it can be concluded that a reaction time of 2 hr or more should be chosen as optimum RCA reaction time, as our AFM results showed that for RCA reactions for more than 2 hr, there were many fully developed RCA chains for signal enhancement; however, a longer reaction time is not desirable since it would not allow for fast turn‐around detections (Jiang, Zou, & Cao, ). Therefore, a reaction time of 2 hr was determined to be an optimal RCA reaction time in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the results from the AFM study, it can be concluded that a reaction time of 2 hr or more should be chosen as optimum RCA reaction time, as our AFM results showed that for RCA reactions for more than 2 hr, there were many fully developed RCA chains for signal enhancement; however, a longer reaction time is not desirable since it would not allow for fast turn‐around detections (Jiang, Zou, & Cao, ). Therefore, a reaction time of 2 hr was determined to be an optimal RCA reaction time in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Because traditional plate culture methods for pathogen detection are time‐consuming, and molecular methods such as enzyme‐linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) require lengthy and labor‐intensive cell enrichment and DNA extraction procedures, developing an efficient and sensitive detection method for E. coli O157:H7 represents a pressing issue. Since the late 1980s, lab‐on‐a‐chip has attracted growing research interests for sensitive detection applications (Foudeh, Didar, Veres, & Tabrizian, ; Jiang, Zou, & Cao, ). In a microfluidic biosensing system, antibodies, nucleic acids, aptamers, or bacteriophages are the main recognition elements to identify target analytes (Jiang, Zou, & Cao, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This article reviews recent developments (last 5 years) on LOC systems for aptamer-based biosensing. We refer the readers to other previously published review articles that cover materials exclusively on either aptamer-based biosensing [27] or microfluidics-based biosensing [28][29][30][31][32][33][34]. Furthermore, although a LOC system typically comprises many analysis components such as sample collection, separation, filtration, mixing, and detection to name a few, as aptamers are used primarily as receptors for target biomolecules, this article will focus on the sensing component of the LOC that utilizes aptamers.…”
Section: Introductionmentioning
confidence: 99%